Asuhan Kesehatan Gigi dan Mulut dengan Kegiatan Promotif dan Preventif di Pondok Pesantren Raudhatun Nasyi`in di Banjarbaru - siti sabatul Habibah; danan; Metty Amperawati; Naning Kisworo Utami; Bunga Nurwati; Rasuna Ulfah; Sri Nuryati; Waljuni Astu Rahman; Isnawati (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2026)
The oral health of the Indonesian people still requires serious attention from healthcare professionals, both doctors and dental nurses. This is evident in the fact that 90% of the Indonesian population still suffers from dental and oral diseases. The most common oral diseases in Indonesia are periodontal disease and dental caries (Ministry of Health of the Republic of Indonesia, 2014, Cit. Tunggadewi, G., 2015). A survey of lecturers in the Dental Nursing Department on March 29, 2021, at the Raudhatul Nasyi'in Islamic Boarding School in Banjarbaru, found an average caries rate of 4.1, categorized as high. The goal of this Community Service Program, through partnerships, is to improve tooth brushing behavior and increase knowledge about dental health, so that the community is willing and able to practice good oral health practices. This also contributes to reducing the rate of dental caries at the Raudhatul Nasyi'in Islamic Boarding School in Banjarbaru. The results achieved during the community service activities, for counseling, were attended by all students and students actively participated during the counseling, resulting in an increase in knowledge. Toothbrushing sessions were held four times. During the activity, counseling was provided on proper tooth brushing techniques. The core activity of this community service was achieving the target (60%) for caries repair or caries fillings, conducted inside the building and outside the building at the dental clinic for 18 days with 5 students visiting each time. Of the 120 students, 90 students (75%) participated. The conclusion is that knowledge about dental and oral health has increased from 50% to 90%. This shows an improvement in gingivitis cases, with the target of 60% achieved. In caries cases, the target of 75.8% was exceeded. It is recommended that the nearest dental and oral health officer collaborate with the Pospen (Education Post) to provide programmed counseling to further improve the dental and oral health of students at the Raudhatun Nasyi'in Pospen. For teeth with caries, treatment should be taken at the nearest Community Health Center.